PROTOTYPE SOLAR CELL AND HYDROPOWER HYBRID ENERGY STATION AS A POWER SUPPLY FOR PUBLIC STREET LIGHTING BASED INTERNET OF THINGS (IoT) USING ANT COLONY OPTIMIZATION (ACO) ALGORITMA - Rasendriya, Ailsa Shafa Nansha; Hartono, Hartono; Harianto, Didi (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
An increase in population in an area can cause an electrical energy crisis due to the increasing number of electrical energy customers. In addition, the use of fossil energy will also decrease, so alternative energy from renewable energy power supply is needed. The challenge is that combining the potential of renewable energy power supply with generators requires a hybrid power plant. A hybrid system with a generator as energy backup is considered sub-optimal because when the power generator is in deficit, it takes over all the wasted power from the renewable energy generation. The purpose of this prototype is to make it easier for technicians to monitor the hybrid power plant, where monitoring is done via Android using the Internet of Things. With remote monitoring, efficiency will increase compared to direct monitoring. Based on the data obtained, the voltage measurement on the Solar Cell shows that the voltage and current move from the lowest value of 11.51 V, continuing to increase until it reaches the highest value of 17.54 V.